Plan estratégico para el desarrollo institucional de la comisión nacional de transporte, tránsito y seguridad vial del cantón Quevedo para el periodo 2014 - 2016 - Molina Plúas, Danny Juan (2015)
This research was conducted with the aim of improving the services of the National Commission on Land Transport, Traffic and Road Safety Quevedo Canton province of Los Ríos, for which a situational analysis was performed to identify weaknesses in the organization. Through which aims to solve the problem of lack of - the following work entitled "2016 STRATEGIC PLAN FOR INSTITUTIONAL DEVELOPMENT OF THE NATIONAL COMMISSION OF TRANSPORTATION, TRAFFIC AND ROAD SAFETY OF CANTON QUEVEDO FOR THE PERIOD 2014" presents administrative tool that allows the organization to improve customer service and get their institutional development. In developing research qualitative and quantitative evaluation is applied to determine the percentage of the characteristics of the investigated object by personal interview based on questionnaires made the head of the organization, I was working with a sample of 379 customers of the company, and with the universe of employees who were surveyed to achieve the objectives of this study. A SWOT analysis was performed to detect the reality of the Organization, both the internal environment by identifying strengths and weaknesses and the external environment with the recognition of the opportunities and threats within various environments….